Psychological and pedagogical support of a child with ASD - Semago N.Ya.; Solomakhina E.A. (Аутизм и нарушение развития, 2017)
Present article considers basic problems which emerge in training and adaptation in the environment of school age children with autism spectrum disorders (ASD). The necessity of prolonged psychological and pedagogical support of an autistic child in an educational organization is substantiated. The main tasks of support specialists (psychologist, speech therapist, special education teacher, tutor, social educator and in¬clusion coordinator), who create conditions and accompanying educational process of children with ASD, are listed.